Pengaruh Media Sosial dan Jejaring Sosial dalam Pengambilan Keputusan Konsumen Produk Baju Olahraga Sepeda di Bandung - Velia Augustina; Felicia Abednego (Jurnal Ilman: Jurnal Ilmu Manajemen, 2022)
Pandemic has huge impacts to the world, not only bad impact, but also good impact. Good impact of pandemic has been identified in several sectors, one of them is on cycling sports. The rising of cycling sports also has a potential effect to cycling fashion apparels. This product were categorized in niche market and to know more information about this product especially in pandemic era, people should be join in social media and social networking because people were limited to do social action. This research aims to know the influence of social media and social networking towards purchase decision on cycling sports clothes brand in Bandung. Primary data were gathered from 150 respondents in Bandung who are actively riding bicycle. The data were processed using SPSS, and were analyzed using multiple regression linear test and the result indicates that social media and social network has a significant impact on purchase decision of cycling sports fashion apparels.